Survey of delivery room resuscitation practices at tertiary perinatal centers in Japan. Issue 2 (25th November 2014) - Hosono, Shigeharu; Tamura, Masanori; Kunikata, Tetsuya; Wada, Masaki; Kusakawa, Isao; Ibara, Satoshi
Abstract Background The aim of this study was to determine the current neonatal resuscitation practices for term infants in Japan, immediately before the 2010 publication of the international neonatal resuscitation consensus. Methods In January 2010, a 26‐question survey was mailed to neonatal department directors. Results A total of 287 neonatal departments were identified. Four surveys were returned as undeliverable. A total of 191 surveys were returned completed, but four departments had no labor and delivery rooms (66.6% response rate, 65.2% survey available response rate). Flow‐inflating bags were most commonly used (63.2%), followed by self‐inflating bags (35.8%), and T‐piece resuscitators (1.0%). Among the participants, 42.1% used oxygen blenders, 56.2% used pure oxygen for initial resuscitation, and 79.5% used a pulse oximeter to change the fraction of inspired oxygen. Among the participants, 45.3% used carbon dioxide detectors to confirm intubation, 42.5% routinely used the detectors, and 55.2% used them when confirming a difficult intubation. In addition, 42.5% of the participants used continuous positive airway pressure to treat breathing problems, most commonly with flow‐inflating bags (93.2%). Conclusions The equipment and techniques used in Japanese perinatal center delivery room resuscitation practices are highly varied. Further research is required to determine which devices and techniques are appropriate for this important and common intervention.